SURROGATE MOTHER DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Mr. Muntaha (Fakultas Hukum Universitas Gadjah Mada, 2013)
The development of science and technology, in particular in the field of health, has already recently brought a huge advantage and problem in human life. An example of technological marvel that not only requires deep legal thoughts but also at the same time solution is the bio-medical technology advancement of surrogacy. Surrogacy deals with human’s inclination towards reproductive activity. However, it opens up legal complication, in particular with regards to the potential commission of a criminal action as well as to the notion of doctor’s liability. Perkembangan ilmu dan teknologi di bidang kesehatan yang semakin maju dan pesat telah membawa berbagai manfaat dan masalah dalam kehidupan manusia dewasa ini. Salah satu perkembangan yang tidak hanya membutuhkan pemikiran di bidang hukum, tetapi juga sekaligus solusinya adalah mengenai kecanggihan teknologi bio-medis surrogate mother. Surrogacy menyentuh sisi kemanusiaan seorang insan terhadap reproduksi. Akan tetapi, lembaga surrogacy juga membawa komplikasi hukum terutama terkait dengan potensi tindak pidana dan dengan persoalan tanggung jawab dokter.